2019
DOI: 10.12659/msm.913504
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Potassium Intake with the Development of Chronic Kidney Disease and Renal Function in Patients with Mildly Decreased Kidney Function: The Korean Multi-Rural Communities Cohort Study

Abstract: BackgroundDietary potassium has negative outcomes in patients with mildly impaired kidney function, while having positive outcomes in patients with hypertension. The association of dietary potassium intake with chronic kidney disease (CKD) development, with presence of hypertension, was studied in the Korean rural population with mildly impaired kidney function.Material/MethodsFrom 3 rural areas of Korea, 5064 participants age ≥40 with CKD stage 2 at baseline were recruited. Patients were classified according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
0
11
0
3
Order By: Relevance
“…Contrary to sodium, potassium intake is emphasized in the DASH diet. A prospective cohort study in South Korean adults with impaired kidney function found that a higher potassium intake was associated with a decreased risk of CKD development and less estimated glomerular filtration rate (eGFR) decline, but only in participants with hypertension [ 60 ]. These findings are corroborated by a cross-sectional study from South Korea, which found that low potassium intake was associated with increased odds of advanced stage CKD, though only in participants with hypertension [ 61 ].…”
Section: The Dash Diet and Chronic Kidney Diseasementioning
confidence: 99%
“…Contrary to sodium, potassium intake is emphasized in the DASH diet. A prospective cohort study in South Korean adults with impaired kidney function found that a higher potassium intake was associated with a decreased risk of CKD development and less estimated glomerular filtration rate (eGFR) decline, but only in participants with hypertension [ 60 ]. These findings are corroborated by a cross-sectional study from South Korea, which found that low potassium intake was associated with increased odds of advanced stage CKD, though only in participants with hypertension [ 61 ].…”
Section: The Dash Diet and Chronic Kidney Diseasementioning
confidence: 99%
“…Two other studies also showed that higher K + intake is associated with better kidney outcomes [ 159 , 165 ], while another study showed no association [ 164 ]. Taken together, the majority of these observational studies demonstrate that diets rich in K + were associated with better kidney outcomes in the overall population or patients with early-stage CKD ( Figure 6 ) [ 151 , 152 , 154 , 155 , 165 , 166 ].…”
Section: Dietary Potassium and Ckdmentioning
confidence: 97%
“…Some cohort studies used food frequency questionnaire to evaluate the association between dietary K + intake and kidney outcomes [ 164–166 ]. For example, Mun et al recently studied the association of dietary K + with eGFR <60 mL/min/1.73 m 2 and >15% decline in eGFR in Korean rural populations with CKD Stage 2 (involving a total of 5064 patients) [ 166 ]. Compared with the subjects in the lowest quartile of dietary K + intake (<1236 mg/day), patients in the highest quartile of dietary K + intake (>2323 mg/day) had a 40% lower risk of CKD development and patients in all quartiles had a 28–46% lower risk of eGFR decline during the follow-up period of 47 months.…”
Section: Dietary Potassium and Ckdmentioning
confidence: 99%
“…Several studies have measured urine potassium excretion as a proxy for dietary potassium intake to assess its effect on clinical outcomes [49,[54][55][56]. Nevertheless, limwww.kjim.org https://doi.org/10.3904/kjim.2020.408 ited data are available supporting the idea that dietary potassium restriction improves the outcomes of patients with CKD [57][58][59], and most recommendations are based on opinions. The 2015 American Dietary Guidelines Advisory Committee report recommends a daily potassium intake of 4,700 mg (121 mmol) for healthy adults [60].…”
Section: Potassiummentioning
confidence: 99%